Amiodarone-Induced Hypothyroidism - Svetlana A. Chepurnenko; Galina V. Shavkuta; Alina D. Nasytko (Кубанский научный медицинский вестник, 2019)
Aim: to present a clinical case of amiodarone-induced hypothyroidism in a patient with paroxysmal atrial fi brillation.Results. Before taking amiodarone, the patient suffered from subclinical hypothyroidism. The level of thyroid stimulating hormone (TSH) was 6.2 mIU/L, thyroxine (T4) — 9.2 pmol/L. Against the background of taking amiodarone in a maintenance dose of 200 mg per day 5 days a week with a break of 2 days, clinically severe hypothyroidism developed with a TSH level of more than 16 mIU/L. An electrocardiogram (ECG) recorded sinus bradycardia with a heart rate (HR) of 37 beats per minute. Paroxysms of atrial fi brillation have stopped. According to the daily ECG monitoring recorded throughout the sinus rhythm with maximum heart rate of 92 beats/min., minimum of 35 beats/min. The circadian rhythm profi le was correct. No pauses were detected for more than two seconds. Transient atrioventricular block was of 1 degree (during sleep). Ectopic activity was represented by supraventricular extrasystoles 112 per day: 107 single, 1 pair, 1 group. Ventricular extrasystoles: 55 per day: polymorphic, solitary. No diagnostically signifi cant elevation or depression of the ST segment was detected. After the abolition of amiodarone, thyroid function was recovered. Levothyroxine was not prescribed. However, paroxysms of atrial fi brillation began to occur again. For the prevention of paroxysms, sotalol 160 mg per day was prescribed.Conclusion. Thus, the development of clinically pronounced amiodarone-induced hypothyroidism has contributed to the existing thyroid dysfunction in the patient. The assessment of the thyroid gland function and its further monitoring in the process of taking the drug is prescribed. Amiodarone therapy is performed in case of ineffectiveness of other antiarrhythmic drugs and, as a rule, is not used for primary prescription.